In vitro Assessment of the Effects of Silybin on CYP2B6-mediated Metabolism - Zhang, Wenwen; Zhang, Yice; Wen, Chengming; Jiang, Xuehua; Wang, Ling (Planta Medica, 2023)
Silybin is a flavonol compound with a variety of physiological properties, such as hepatoprotective, anti-fibrogenic, and hypocholesterolemic effects. Although the in vivo and in vitro effects of silybin are frequently reported, studies on herb–drug interactions have yet to be performed. With the discovery of multiple important substrates of CYP2B6 recently, there is a growing body of evidence indicating that CYP2B6 plays a much larger role in human drug metabolism than previously thought.The purpose of this study is to determine how silybin affects the CYP2B6 enzymeʼs activity, as well as to clarify the molecular mechanisms for inhibition by silybin. The results showed that silybin inhibited CYP2B6 activity in liver microsomes in a non-competitive manner, with IC50 and Ki values of 13.9 µM and 38.4 µM, respectively. Further investigations revealed that silybin could down-regulate the expression of CYP2B6 protein in HepaRG cells. The hydrogen bond conformation of silybin in the active site of the CYP2B6 isoform was revealed by a molecular docking study. Collectively, our findings verify that silybin is an inhibitor of CYP2B6 and explain the molecular mechanism of inhibition. This can lead to a better understanding of the herb–drug interaction between silybin and the substrates of the CYP2B6 enzyme, as well as a more rational clinical use of silybin.
Keywords: silybin; Silybum marianum; CYP2B6; inhibition; Liver microsomes; Interaction